First record of the non-indigenous mussel Limnoperna fortunei (Bivalvia, Mytilidae) as an epibiont of the crab Trichodactylus borellianus (Decapoda, Trichodactylidae) - Rojas Molina, Florencia Mercedes (2013)
In the area of Middle Paraná River, Argentina, in the pleuston community associated with the roots of Eichhornia crassipes (Mart.) Solms-Laubach, 1883, an epibiosis of the non-indigenous mussel Limnoperna fortunei (Dunker, 1857) on the native crab Trichodactylus borellianus Nobili, 1896 was occasionally recorded. The organisms were measured, weighed, and photographed. Attached molluscs were larger and heavier than their host crabs. This new interaction in the system was analyzed with regard to several biological and ecological characteristics of both species.